Democratization a thematic approach - Noakes, Stephen; Wilson, Chris (London Bloomsbury Academic, 2023)
Taking a uniquely theoretical approach, this textbook offers an accessible introduction to the subject of democratization and the challenges facing its progress"--
Introduction: Democratization in An Era of Pessimism and Doubt

PART I: DEMOCRATIZATION FROM WITHIN

1. Modernisation and Its Discontents
2. Historical Sociology and Transition Studies
3. Conflict and Democracy: Politics in Divided Societies
4. Democratization from Below: Civic Culture and Civil Society
5. Illberal Democracy and Competitive Authoritarianism

PART II: DEMOCRATIZATION FROM WITHOUT

6. Threats to Democracy: Backsliding, Coups and Populism
7. Globalization and Democracy
8. Funding Change: International Democracy Assistance
9. After the 'End of History'?
Includes bibliographical references and index.
Keywords: Democratization; Authoritarianism -- 21st century; Populism -- 21st century